PELAKSANAAN HUKUM WARIS ISLAM PADA MASYARAKAT BATAK TOBA (STUDI DI KOTA MEDAN) - MIKA LESTARI (PREMISE LAW JURNAL, 2014)
ABSTRACT Inheritance occurs when someone who is married legally dies. The distribution of inheritance is closely related to the family structure in Indonesia which has three types: patrilineal family structure, matrilineal family structure, and parental family structure. If someone dies, there will be a correlation between him, the person who is still alive, the heir, and the inheritance. In the case of inheritance, there are adat law and the Islamic law, and these laws are in effect on Batak Toba people who are Moslems, they have to comply with the Islamic Law on Inheritance. The result of the research showed that the implementation of the Islamic law on Inheritance in Batak Toba community in Medan had not yet used the Islamic law completely, for some of the still used adat law. The awareness of law should encourage Batak Toba community in Medan to use the Islamic law because the implementation of the Islamic law is a part of their belief and becomes their obligation to comply with. The dispute which occurs to heirs of Batak Toba in Medan is usually consulted to one of the family members who are considered the oldest member. If there is no resolution of the dispute, the case will be brought to the Religious Court. Keywords: Inheritance of Batak Toba, Dispute of Inheritance